2017
DOI: 10.1111/lang.12236
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Distribution of Practice for the Acquisition of L2 Morphology: A Conceptual Replication and Extension

Abstract: This study examined optimal learning schedules for second language (L2) acquisition of a morphological structure. Sixty participants studied the simple and complex morphological rules of a novel miniature language system so as to use them for oral production. They engaged in four training sessions in either shorter spaced (3.3‐day interval) or longer spaced (7‐day interval) learning conditions. From the beginning of the third training session, the 3.3‐day interval group started to provide more accurate target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(114 citation statements)
references
References 45 publications
8
105
1
Order By: Relevance
“…Regarding the effects of ISI on the acquisition of the target skill in oral picture naming from meaning to articulation, it was found that ISI only had an effect on the pre‐session performance in oral picture‐naming accuracy at the beginning of TS2 and TS3, but did not show effects on the post‐session performance at the end of the two TSs, in terms of either accuracy (at the end of both TS2 and TS3) or RTs (at the end of TS3). The short 1‐day ISI resulted in much less forgetting or degradation in oral picture‐naming accuracy between sessions than the longer 1‐week ISI, which is consistent with the similar finding from Suzuki (). This is logical because longer gaps tend to lead to more forgetting, especially since knowledge by the end of TS1 largely remained at the declarative level, and declarative knowledge is vulnerable to forgetting.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the effects of ISI on the acquisition of the target skill in oral picture naming from meaning to articulation, it was found that ISI only had an effect on the pre‐session performance in oral picture‐naming accuracy at the beginning of TS2 and TS3, but did not show effects on the post‐session performance at the end of the two TSs, in terms of either accuracy (at the end of both TS2 and TS3) or RTs (at the end of TS3). The short 1‐day ISI resulted in much less forgetting or degradation in oral picture‐naming accuracy between sessions than the longer 1‐week ISI, which is consistent with the similar finding from Suzuki (). This is logical because longer gaps tend to lead to more forgetting, especially since knowledge by the end of TS1 largely remained at the declarative level, and declarative knowledge is vulnerable to forgetting.…”
Section: Discussionsupporting
confidence: 88%
“…The ISIs and RIs were set up in this way also to make sure that the ISI:RI ratio fell within the range of 10–30% for only one of the groups for the short‐term RI and one for the long‐term RI. It should be noted that RI in this study was treated as a between‐subject variable, rather than a within‐subject variable, in order to avoid the confounding effect of retesting (i.e., the first posttest may serve as another learning opportunity; see Suzuki, , for discussion). This is a methodological improvement over all previous SLA research on L2 complex skill learning.…”
Section: The Present Studymentioning
confidence: 99%
“…They observed an advantage for the shorter ISI, in terms of response speed on an oral picture‐description task at delayed posttest (28‐day RI). Extending these findings, Suzuki () observed superior gains in accuracy on an oral production task for a 3.3‐day group compared to a 7‐day group at delayed posttest (28‐day RI) for the learning of simple and complex morphology within an artificial language system.…”
Section: Literature Reviewmentioning
confidence: 86%
“…A number of cognitive psychology studies have been conducted to identify the most effective practice schedule (see Cepeda et al., for review). This line of investigation also has potential to enhance L2 learning, and the field has seen a surge of interest in this issue (Bird, ; Nakata, ; Nakata & Suzuki, ; Rogers, ; Serrano & Huang, ; Suzuki, ). The current special issue presents two innovative studies that further advance our understanding of the role of practice distribution.…”
Section: Defining and Extending Research Areas For L2 Practicementioning
confidence: 99%
“…The learning processes and outcomes of different practice conditions also need to be understood from a variety of angles. First, research on the effectiveness of L2 practice should reveal the learning process or trajectory, as well as the outcome of practice (Nakata & Suzuki, ; Suzuki, ). According to the desirable difficulty framework in cognitive psychology (Schmidt & Bjork, ; Soderstrom & Bjork, ), performance level during the practice phase does not always predict the retention of knowledge and skills over time.…”
Section: Defining and Extending Research Areas For L2 Practicementioning
confidence: 99%